Groundwater Contamination of Heavy Metals through Soil Attenuation - Crump, Naomi; McGilligan, Tobin; Schumacher, Dan; Calkins, Cody (My University, 2016)
In Wisconsin, two-thirds of the population relies on groundwater for their drinking water supply, and this resource is threatened by heavy metal contamination from industrial waste, landfills, and other sources. Our goal is to assess the vulnerability of Wisconsin groundwater to heavy metal contamination around four Environmental Protection Agency (EPA) ‘Superfund’ sites by improving a previous soil attenuation model with knowledge from contemporary research.
Includes figures, maps, tables, charts, appendices, bibliography
Keywords: Contamination; Heavy Metals; Groundwater; Soil Attenuation